IMPLEMENTATION OF A WEB-BASED APPLICATION FOR THE RECORDING OF GOODS IN THE STORAGE COMPARTMENT OF TOOLS AND CONSUMABLES IN KABUPATEN PATI - Aan Ardiansyah; Mashudi Mashudi (International Journal of Artificial Intelligence for Digital Marketing, 2024)
BPBD Pati Regency in recording goods in the warehouse uses goods control cards and miscosoft excel as a medium for recording goods. The recording process already has its own procedures so that incoming and outgoing goods can be recorded accurately. However, despite using technology in recording goods in the warehouse, the recording of goods is still not optimal because the lack of coordination between logistics staff makes the recording of goods slow. This results in a mismatch between the stock in the system and the stock in the warehouse. The purpose of this study is to assist logistics staff in recording incoming and outgoing goods so that the recording process can run efficiently and can increase warehouse productivity using web-based applications. This type of research is a case study using qualitative methods. The result of this research is a web-based application for recording goods in the tools and food ingredients warehouse at BPBD Pati Regency. The design of this application uses context diagram, data flow diagram level 0 (DFD Level 0), data flow diagaram level 1 (DFD Level 1) and entity relationship diagram (ERD). The programming language used is PHP and the database uses MySQ.